SASARAN STRATEGIS PENGEMBANGAN MODEL KLUSTER INDUSTRI PERIKANAN TANGKAP (Strategic objectives for Cluster Development Model of Capture Fisheries Industry) - Tri Wiji Nurani; . Ardani; Ernani Lubis (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2014)
ABSTRACTCluster model in fisheries industry base on leading commodity is a policies initiated by the Ministry of Fisheries and Marine Affairs to promote the accelerated development of marine and fisheries sector. Palabuhanratu is one of the areas designated as fisheries industry cluster development. The successful development of the program needs to be evaluated by measurable indicators. This study aims to formulate strategic goals as a measure of the success of the development model of capture fisheries industrial clusters in Palabuhanratu. SWOT analysis and balanced scorecard are used to formulate a strategy and a benchmark for the success of the program. The study states that the strategic objectives of capture fisheries industry cluster development in Palabuhanratu should be able to synergize the interests of actors and interests among sectors in order to create industries competitiveness and productiveness. Factors of successinclude8 strategic targets with 17 benchmarks are covered in 4 perspectives: customer and stakeholder perspective, financial, internal business and institutional perspective. Strategic objectives include balancing utilization and conservation, continuity of production, quality, customer satisfaction, supply chain integration, partnerships, and commitment among the actors in the development of the program.Keywords: cluster industry model, Palabuhanratu, capture fisheries, strategic objective, benchmark-------ABSTRAKModel kluster industri perikanan berbasis komoditas unggulan merupakan kebijakan yang digulirkan oleh Kementerian Kelautan dan Perikanan untuk mendorong percepatan pembangunan sektor kelautan dan perikanan. Palabuhanratu merupakan salah satu lokasi yang ditetapkan sebagai kawasan pengembangan kluster industri perikanan tangkap. Keberhasilan pengembangan program perlu dievaluasi melalui indikator yang terukur. Penelitian ini bertujuan untuk memformulasikan sasaran strategis sebagai tolok ukur keberhasilan pengembangan model kluster industri perikanan tangkap di Palabuhanratu. Analisis SWOT dan balanced scorecard digunakan untuk merumuskan strategi dan tolok ukur keberhasilan program. Hasil penelitian menyatakan bahwa sasaran strategis pengembangan kluster industri perikanan tangkap di Palabuhanratu harus dapat mensinergikan kepentingan para pelaku dan kepentingan antar sektor untuk dapat menciptakan industri yang memiliki daya saing dan produktif. Faktor keberhasilan mencakup 8 sasaran strategis, dengan 17 tolok ukur keberhasilan yang tercakup dalam 4 perspektif yaitu perpektif pelanggan dan stakeholder, keuangan, bisnis internal dan perspektif kelembagaan. Sasaran strategis meliputi keseimbangan pemanfaatan dan konservasi, kontinuitas produksi, mutu, kepuasan pelanggan, integrasi rantai pasok, kemitraan, dan komitmen diantara para pelaku dalam pengembangan program.Kata kunci: model kluster industri, Palabuhanratu, perikanan tangkap, sasaran strategis, tolok ukur